Tissue metabolomics study to reveal the toxicity of a traditional Tibetan medicine 'Renqing Changjue' in rats. Issue 66 (8th November 2018) - Xu, Can; Wang, Yingfeng; Rezeng, Caidan; Zhang, Lan; Zhao, Baosheng; Wang, Xia; Wu, Xiuyuan; Li, Zhongfeng; Chen, Jianxin
Abstract : Combinatorial tissue metabolomics technique using NMR and ICP-MS to investigate the effect of RQCJ in rats. Abstract : Renqing Changjue (RQCJ), a precious Traditional Tibetan Medicine (TTM), has been widely used in the management of diseases of the digestive system, toxinosis and pyreticosis. However, in the formula, a significant level of heavy metals, which are potential toxic elements, are present. Therefore, it is important to assess the toxicity of RQCJ dynamically and holistically. In the present study, a 1 H NMR metabolomics approach and inductively coupled plasma mass spectrometry (ICP-MS) were implemented to analyze the samples of liver, kidney and spleen from rats treated with RQCJ. The results revealed that 9 metabolites in the liver, 13 metabolites in the kidney and 16 metabolites in the spleen were significantly altered, which suggest that disturbances in TCA cycle, amino acid metabolism, energy metabolism and oxidative stress are produced by successive administration of RQCJ over 15 days. Complemented by histopathology and biochemical assay, the trends of the metabolite levels indicate that RQCJ caused tissue injury to a certain extent, which was evidenced by the high levels of As and Hg in the tissue. The toxic effects of RQCJ were alleviated in liver and kidney during the recovery period, and RQCJ may cause long-term damage in spleen. These findings provide a significant experimental proof on the estimated safety and valuable information about the metabolism of RQCJ, which will be valuable in determining the health risks of the drug.